2018
DOI: 10.1111/are.13760
|View full text |Cite
|
Sign up to set email alerts
|

Effect of date palm (Phoenix dactylifera ) seed extract as a dietary supplementation on growth performance immunological haematological biochemical parameters of common carp

Abstract: This study aimed to assess the effect of date palm (Phoenix dactylifera) seed (DPS) extract at 0.5%, 1%, 2% and 4% as a dietary supplement over 60 days, on the growth and immune-physiology of common carp (Cyprinus carpio) fingerlings. The weight gain in fish fed with 0.5% DPS was significantly greater than other treatments and fish fed a control diet with no DPS (p < 0.05). With increasing DPS dosage above 0.5%, weight gain and growth rate gradually declined. Feed conversion ratio in fish fed 0.5% DPS was lowe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 34 publications
0
27
0
Order By: Relevance
“…In aquaculture, besides immune stimulants properties, plant extracts have been widely used due to their beneficial impacts on fish growth performance (Mohammadi et al, ; Soltani, Lymbery, Song, & Hosseini Shekarabi, ). Citrus fruit peels extracts are the richest source of flavones and flavonoid, and could improve the immune system and haemato‐biochemical parameters of fish species (Youssef, Youssef, Mousa, & Health, ).…”
Section: Introductionmentioning
confidence: 99%
“…In aquaculture, besides immune stimulants properties, plant extracts have been widely used due to their beneficial impacts on fish growth performance (Mohammadi et al, ; Soltani, Lymbery, Song, & Hosseini Shekarabi, ). Citrus fruit peels extracts are the richest source of flavones and flavonoid, and could improve the immune system and haemato‐biochemical parameters of fish species (Youssef, Youssef, Mousa, & Health, ).…”
Section: Introductionmentioning
confidence: 99%
“…The previous report indicated that Pacific white leg shrimp fed the diet containing S. cumini leaf power at 1% for 28 days produced a significant enhancement of growth indices including WG, SGR, and protein efficiency ratio compared with the control (Prabu et al, 2018). Mohammadi et al (2018) found that common carp (Cyprinus carpio) fed the diets containing 0, 0.5, 1, 2, and 4% date palm (Phoenix dactylifera) seed extract for 60 days showed a significant improvement in growth parameters and feed utilization efficiency. In this research, the underlying mechanisms of action of herbal plants on the growth of fish are not well understood.…”
Section: Discussionmentioning
confidence: 98%
“…In this research, the underlying mechanisms of action of herbal plants on the growth of fish are not well understood. Such reports indicated that active compounds found in the plant extracts may potentially improve feed intake, nutrient digestion, metabolism, and absorption capacity of the nutrients by increasing the activities of certain intestinal digestive enzymes (Haghbayan and Mehrgan, 2015;Mohammadi et al, 2018;Sewaka et al, 2019). Furthermore, scientific studies have demonstrated that positive effects of diets supplemented with phytogenic additives would directly induce the expression of growth hormone (GH) and insulin-like growth factors (IGFs) mRNA in order to promote muscle cell proliferation and differentiation, resulting in a pronounced increase in the growth rate of fish (Sruthi et al, 2018;Ahmadifar et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations